Analisis Kepuasan Nasabah Terhadap Kualitas Jasa Pelayanan: PT. Bank Perkreditan Rakyat Shinta Daya Yogyakarta - Indah Datin Nadliroh; Agus Wiastono; Arief Setyo Bakty (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
The quality of service provides an incentive to customers to establish a strong bond with the company. This kind of bond in the long term allows the company to thoroughly understand the customer's expectations and needs, thus the company can increase customer satisfaction where the company maximizes a pleasant customer experience and minimizes a less pleasant customer experience. The purpose of this research, it is to find out how to analyze the quality of service (tangibles, reliability, responsiveness, assurance, and empathy) toward customer satisfaction at the PT. Bank Sinar Mas Gorontalo Branch and in this research using Multiple Simple Regression Analyses. The results of the validity instrument testing show that r-hitung > r-tabel means valid and reliability is above 0.6, which means reliable. The research results show multiple regression analysis, namely, Y = a + 1X1 + 2X2 + 3X3 + 4X4 + 5X5 = 8.209 + (-0.065X1) + 0.252X2 + 0.213X3 + 0.199X4 + 0.2875X5. The results of the t-test show that service quality partially has a positive effect on customer satisfaction. The results of the F test show that service quality simultaneously has a positive effect on customer satisfaction, where the P value is 0.000 0.05. The coefficient of determination (R2) shows the contribution of 0.643, or 64.3%, of service quality to customer satisfaction, while the remaining 52.8% is the contribution of other factors that were not examined in this research.